Estimation of the Microaccelerations on an Automatic Rotary Vibration Isolation Device - Andry V. Sedelnikov; Anastasia S. Taneeva; Luiza A. Manukyan (Space: Science & Technology)
The paper investigates the field of microaccelerations inside the protected zone of a microgravity platform of the mechanical principle of action. The platform is a 2-stage gyroscope. A container with technological equipment is fixed on the inner frame. A model of the microacceleration field in the working area of the technological equipment during the implementation of the directed crystallization process is constructed. In a simulation, data from assessments of the parts of the angular velocity direction of the rotation of the small spacecraft “Aist-2D” were used. Using these data, a microacceleration model was constructed and a microgravity platform control law was developed. When implementing this control law, near-zero values of microaccelerations are obtained inside the protected zone of the microgravity platform. These results can be used for small spacecraft missions.